Good response to pulsed dye laser in patients with capillary malformation‐arteriovenous malformation syndrome (CM‐AVM). Issue 2 (15th January 2020) - Iznardo, Helena; Roé, Esther; Puig, Luis; Vikula, Mikka; López‐Sánchez, Cristina; Baselga, Eulalia
Abstract: Capillary malformation‐arteriovenous malformation syndrome (CM‐AVM) is an autosomal dominant disorder caused by heterozygous mutations in RASA1 and EPHB4 . Capillary stains in CM‐AVM are compatible with Schöbinger's phase I AVMs. Vascular laser has been classically contraindicated for the treatment of AVMs, as there is a fear of accelerating their progression. In this study, we have treated capillary stains in five CM‐AVM patients with pulsed dye laser, with improvement and without worsening or recurrence of the lesions after 1 year of clinical and ultrasound follow‐up.